2016
DOI: 10.4244/eij-d-16-00386
|View full text |Cite
|
Sign up to set email alerts
|

In-hospital and midterm clinical outcomes of rotational atherectomy followed by stent implantation: the ROTATE multicentre registry

Abstract: RA appears to be safe and effective with acceptable in-hospital and follow-up MACE considering the severity of patient and lesion characteristics. DES implantation following RA was associated with a reduction in MACE during the follow-up period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
46
6
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(69 citation statements)
references
References 21 publications
13
46
6
4
Order By: Relevance
“…Our analysis of over 300,000 PCI procedures represents a large sample size; therefore, the results may be more reliable and could serve as additive knowledge for patients requiring RA treatment. Data from Kawamoto et al reveled that after exclusion of STEMI patients, in‐hospital rate of cerebral stroke was 0.3%, MI 7.4%, death 0.6%, and MACE 8.3%, which was much higher as compared with our population: MI ‐ 0.17%, death—0.17% and MACCE—0.59%. It is definitely to a great extent caused by underestimation resulting from not including patients from further parts of the entire hospitalization.…”
Section: Discussioncontrasting
confidence: 50%
“…Our analysis of over 300,000 PCI procedures represents a large sample size; therefore, the results may be more reliable and could serve as additive knowledge for patients requiring RA treatment. Data from Kawamoto et al reveled that after exclusion of STEMI patients, in‐hospital rate of cerebral stroke was 0.3%, MI 7.4%, death 0.6%, and MACE 8.3%, which was much higher as compared with our population: MI ‐ 0.17%, death—0.17% and MACCE—0.59%. It is definitely to a great extent caused by underestimation resulting from not including patients from further parts of the entire hospitalization.…”
Section: Discussioncontrasting
confidence: 50%
“…22 -24 Another multicenter registry reported a rate of all-cause death after RA of 5.0% at 1 year and 9.5% at 2 years. 13 This difference might be explained by the fact that the present subjects included more high-risk patients who were elderly (mean age, 70 years) with high offered a high rate of procedural success, a high incidence of follow-up MACE was observed. Multivariate analysis identified age and CKD including hemodialysis as strong independent predictors for both MACE and cardiac death.…”
Section: Discussionmentioning
confidence: 85%
“…23 Kawamoto et al recently reported hemodialysis as the strongest predictor of MACE at 2-year follow-up. 13 Kyono et al also reported that both angiographic and clinical outcomes were still suboptimal for highly complex, severely calcified lesions requiring RA in patients with hemodialysis, even when using DES. 25 The present study provides one of the largest sets of observational data with the longest follow-up period, and confirms a 21.5% rate of cardiac death, similar to other registry data from smaller samples with shorter follow-up.…”
Section: Long-term Clinical Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the ROTATE registry, 1,076 consecutive patients from 9 sites in Italy and Japan underwent RA, 37.3% as a primary strategy and 30% for initial device failure . Procedural success was very high (99.1%) with a relatively low complication rate of dissection (7%), perforation (1%), or slow/no‐flow (1.1%).…”
Section: Rotational Atherectomymentioning
confidence: 99%